Particle strengthening of the surface of copper electrode for electrical discharge machining. (14th January 2008) - Guo, D.M.; Zhang, M.; Jin, Z.J.; Zuo, B.X.
The manufacture of Electrical Discharge Machining (EDM) electrodes for the machining of mould cavities is often an intractable problem, which consumes much money and time. The combination of Rapid Prototyping (RP) with electroforming paves a way to fabricate copper EDM electrodes more rapidly and economically. However, the spark-resistance of the electroformed copper electrode is still not satisfying. To enhance the surface quality of copper electrodes, Cu-ZrB2 composite coating was electrodeposited and the EDM performance of this new material was studied. The hardness of the composite coatings increases with the increase in ZrB2 percentage, whereas the incorporation of ZrB2 particles has little effect on the electrical resistivity of composites. The effects of EDM parameters on the Material Removal Rate (MRR) and Tool Wear Ratio (TWR) of electrodes were investigated. The Cu-ZrB2 composite coating shows better EDM performance than that of the electroformed copper electrode.